The Interpretation of Radio Stations Regarding Ethnic Broadcasts Based on Social Integration in Multi-Ethnic Communities in West Kalimantan - ., Juniawati; ., Pawito; Purwasito, Andrik; Hastjaryo, Sri (Journal of Ecohumanism, 2024)
Social integration is a barometer for ensuring the sustainability of a dynamic and harmonious social life. Ideally, all elements of society create, maintain, and safeguard social integration, including in West Kalimantan-Indonesia. For more than 20 years, West Kalimantan has lived with psychological trauma due to the conflict between Madura and Dayak, Madura and Malay since the era of 1952 - 1997, Madura and Malay in 1999 (Abas, 2002; Asmara, 2002 in Amar, TT, 2007). There have been 17 recorded Dayak-Madurese ethnic conflicts (Kristianus, 2011). Ethnic broadcasts on the radio have becomeemergencyto encourage wakefulness Safe and peaceful life in Indonesia. This paper aims to clarify the interpretation of radio media regarding ethnic broadcasts based on social integration in multi-ethnic communities. Creswell's (2017) interpretive qualitative methodology (Corbin, 2008) with a case study method (K. Yin, 2003). Data collection through in-depth interviews with Dermaga radio in Sekadau Regency and Kenari radio. Research findings: media interpretation of ethnic broadcasts based on social integration: (1) Ethnic broadcasts as an asset of tolerance, (2) Ethnic broadcasts, a form of shared responsibility. The factors that form media interpretations of ethnic broadcasts based on social integration: (1) Pancasila ideology as the basis for ethnic broadcasts, (2) The influence of interests and creativity, (3) Community preferences for cultural values, (4) Community encouragement to collaborate and participate.